Efficacy of neoadjuvant docetaxel + cisplatin chemo-hormonal therapy versus docetaxel chemo-hormonal therapy in patients with locally advanced prostate cancer with germline DNA damage repair gene alterations. (September 2022) - Chi, Chenfei; Liu, Jiazhou; Fan, Liancheng; Zhu, Yinjie; Wang, Yanqing; Sha, Jianjun; Huang, Yiran; Dong, Baijun; Pan, Jiahua; Xue, Wei
Purpose: To assess the efficacy and safety of neoadjuvant docetaxel + cisplatin chemotherapy with androgen deprivation therapy for the treatment of locally advanced prostate cancer (PCa) in patients harboring germline DNA damage repair genes (gDDR) defects. Methods: We conducted a prospective observational study in patients with locally advanced PCa confirmed with gDDR defects through next-generation sequencing. All patients received either docetaxel + cisplatin (platinum-group) or docetaxel chemo-hormonal therapy (docetaxel group) followed by radical prostatectomy with extended lymphadenectomy. The primary end point was biochemical progression-free survival (bPFS) and secondary end points include postoperative pathological response and safety assessment during the study period. Results: A total of 36 patients were included in the study, among whom 14 and 22 patients received docetaxel + cisplatin and docetaxel treatment, respectively. Down-staging of Tumor (T), Nodes (N), and Metastasis (M) stages was observed in 11 (78.57%) and 9 (40.9%) patients ( p = 0.041), respectively, in the docetaxel + cisplatin group and docetaxel group. The median bPFS was 7.76 months (95% CI 0.770–14.748) and not reached in the docetaxel group and docetaxel + cisplatin group, respectively. bPFS was significantly longer in the docetaxel + cisplatin group ( p = 0.039) with a hazard ratio of 0.386 (95% CI 0.151–0.987, p < 0.05). Furthermore, one patient discontinued docetaxel + cisplatin after second cycle due to severe liver insufficiency which was confirmed as viral hepatitis A and no significant perioperative complications was observed in either group. Conclusion: This study suggests that cisplatin may increase docetaxel anticancer activity with tolerable safety profile in patients with locally advanced PCa carrying gDDR defects in the neoadjuvant setting, a hypothesis which will require prospective, randomized confirmation.